Breeding Strategies and Challenges in the Improvement of Blast Disease Resistance in Finger Millet. A Current Review - Mbinda, Wilton; Masaki, Hosea (Frontiers in Plant Science, 2021)
Climate change has significantly altered the biodiversity of crop pests and pathogens, posing a major challenge to sustainable crop production. At the same time, with the increasing global population, there is growing pressure on plant breeders to secure the projected food demand by improving the prevailing yield of major food crops. Finger millet is an important cereal crop in southern Asia and eastern Africa, with excellent nutraceutical properties, long storage period, and a unique ability to grow under arid and semi-arid environmental conditions. Finger millet blast disease caused by the filamentous ascomycetous fungus Magnaporthe oryzae is the most devastating disease affecting the growth and yield of this crop in all its growing regions. The frequent breakdown of blast resistance because of the susceptibility to rapidly evolving virulent genes of the pathogen causes yield instability in all finger millet-growing areas. The deployment of novel and efficient strategies that provide dynamic and durable resistance against many biotypes of the pathogen and across a wide range of agro-ecological zones guarantees future sustainable production of finger millet. Here, we analyze the breeding strategies currently being used for improving resistance to disease and discuss potential future directions toward the development of new blast-resistant finger millet varieties, providing a comprehensive understanding of promising concepts for finger millet breeding. The review also includes empirical examples of how advanced molecular tools have been used in breeding durably blast-resistant cultivars. The techniques highlighted are cost-effective high-throughput methods that strongly reduce the generation cycle and accelerate both breeding and research programs, providing an alternative to conventional breeding methods for rapid introgression of disease resistance genes into favorable, susceptible cultivars. New information and knowledge gathered here will undoubtedly offer new insights into sustainable finger millet disease control and efficient optimization of the crop’s productivity.